Exploring Recent Research on Definitions of the Myanmar Southwest Monsoon: A Comprehensive Bibliographic Overview - Oo, Kyaw Than (Journal of Sustainability and Environmental Management, 2023)
Accurately pinpointing the onset and withdrawal dates of the monsoon bears significant implications for diverse sectors. However, this task is fraught with challenges due to the intricate interannual and spatial variabilities. The Myanmar Southwest Monsoon (MSwM) index emerges as a widely adopted tool for delineating the initiation and cessation of the southwest monsoon across its respective domains. The confluence of advancements in satellite remote sensing, climate modeling, and data assimilation techniques presents opportunities for refining monsoon intensity indices. Additionally, a nuanced comprehension of the intricate interactions between the monsoon and climate teleconnections stands to enhance the assessment of monsoon intensity. Distinguished as a distinct entity from the major South Asian monsoon system, the MSwM follows a seasonal cycle intricately linked to mainland Indochina. The thermal influence of the Tibetan Plateau amplifies both meridional and zonal land-sea thermal contrasts, underscoring the importance of monitoring and anticipating monsoons. The MSwM, a product of complex interactions involving the earth, ocean, atmosphere, hydrosphere, biosphere, and cryosphere, exerts a profound impact on regional facets such as agriculture, ecology, chemistry, economics, and society. As technological strides continue, especially in satellite observations and climate models, avenues open up for refining our understanding of monsoon dynamics. The limitations inherent in the current coupled model of the land-sea-atmosphere system underscore the anticipation for advancements in modeling studies. Research in this domain not only contributes to the regulation of human activities but also fosters a harmonious coexistence between humanity and nature, safeguarding the human habitat.